Sensitization to Fas-mediated apoptosis by dengue virus capsid protein - Thawornchai Limjindaporn (2018)
Dengue fever (DF) and dengue hemorrhagic fever (DHF) are important public health problems in tropical regions. Abnormal hemostasis and plasma leakage are the main patho-physiological changes in DHF. However, hepatomegaly, hepatocellular necrosis and fulminant hepatic failure are occasionally observed in patients with DHF. Dengue virus-infected liver cells undergo apoptosis but the underlying molecular mechanism remains unclear. Using a yeast two-hybrid screen, we found that dengue virus capsid protein (DENV C) physically interacts with the human death domain-associated protein Daxx, a Fas-associated protein. The interaction between DENV C and Daxx in dengue virus-infected liver cells was also demonstrated by co-immunoprecipitation and double immunofluorescence staining. The two proteins were predominantly co-localized in the cellular nuclei. Fas-mediated apoptotic activity in liver cells constitutively expressing DENV C was induced by anti-Fas antibody, indicating that the interaction of DENV C and Daxx involves in apoptosis of dengue virus-infected liver cells. © 2007 Elsevier Inc. All rights reserved.